The role of neutrophilic extracellular traps in oncogenesis - Mereke Maratkyzy; Aruna Kosybaeva; Naylya Kabildina; Anelya Beisenaeva (National Scientific Medical Center, 2019)
Views on the role of extracellular neutrophilic traps in oncology vary greatly. On the one hand, there is evidence of the anticarcinogenic properties of neutrophil networks associated with the direct destruction of tumor cells and stimulation of the immune system. Cytotoxicity towards tumor cells is manifested by trap components (myeloperoxidase, proteinases and histones), while DNA strands are considered as a kind of tool for capturing tumor cells and limiting their further spread.